Matematyka
Konto usunięte
2017-12-31 11:30:49
Oblicz: g) 2 (x - 3) - 4 (3 + x) = - 3 (x + 2) + 2 (2x - 1) wynik powinien wynosić : - 10/3 lub -10/9 h) 6 (x + 1) + 3 (2 - x) = 2 (2x - 1) - (4 - x) wynik powinien wynosić : 9 i) 2 (x - 7) - 3 (x + 2) = 4 (x + 3) + 2 (x - 9) wynik powinien wynosić : -2 j) - 3 (x + 6) - 6 (2x + 8) = - 3 (4 - x) + 9 (x + 8) wynik powinien wynosić : -5 k) - 8 (x + 2) + 3 (x + 5) = - 2 (2x + 3) + 4 (2x - 1) wynik powinien wynosić : 1
Odpowiedź
wiola4897
2017-12-31 14:30:11

g) 2 (x - 3) - 4 (3 + x) = - 3 (x + 2) + 2 (2x - 1)  2x-6-12-4x= -3x-6+4x-2 2x-4x+3x-4x= -6-2+6+12 -3x= 10  / :(-3) x= -10/3 h) 6 (x + 1) + 3 (2 - x) = 2 (2x - 1) - (4 - x) 6x+6+6-3x= 4x-2-4+x 6x-3x-4x-x= -2-4-6-6 -2x= -18  /:(-2) x=9 i) 2 (x - 7) - 3 (x + 2) = 4 (x + 3) + 2 (x - 9) 2x-14-3x-6= 4x+12+2x-18 2x-3x-4x-2x= 12-18+6+14 -7x= 14  /:(-7) x=-2 j) - 3 (x + 6) - 6 (2x + 8) = - 3 (4 - x) + 9 (x + 8) -3x-18-12x-48= -12+3x+9x+72 -3x-12x-3x-9x= -12+72+48+18 -27x= 126 / :(-27) x= - 4 18/27    mnie tak wychodzi, a nie -5 k) - 8 (x + 2) + 3 (x + 5) = - 2 (2x + 3) + 4 (2x - 1) -8x-16+3x+15= -4x-6+8x-4 -8x+3x+4x-8x= -6-4-15+16 -9x= -9  /:(-9) x=1

Dodaj swoją odpowiedź